NOC Based Router Architecture Design Through Decoupled Resource Sharing Using CABHR Algorithm - A. Kalimuthu; M. Karthikeyan (Institute of Advanced Engineering and Science, 2017)
A Network-on-Chips (NoCs) is rapid promising for an on-chip alternative designed in support of many-core System-on-Chips (SoCs). In spite of this, developing an increased overall performance low latency Network on chip using low area overhead has always been a new challenge. Network on Chips (NoCs) by using mesh and torus interconnection topologies have become widely used because of the easy construction. A torus structure is nearly the same as the mesh structure, however, has very slighter diameter. In this regard, we propose effective router design for Decoupled Resource sharing in a torus topology based on clustering algorithms Based Hierarchical Routing (CABHR) to get better the efficiency of NoC. We show that our approach is provides improved latency and energy consumption, overall performance developments compared to the most distinguished existing routing technique